Post occupancy assessment comparative analysis towards sustainable township development - Yaman, Rostam; Rahman, Sarah; Ismail, Farrah Zuhaira; Salleh, Siti Aekbal; Ahmad, Noraini; Thadaniti, Suwattana (Malaysian Institute of Planners, 2023)
Sustainable township development is the foundation of a sustainable society; however, the development of sustainable neighbourhoods as it currently stands will not permit all stakeholders, particularly end users, to effectively address current or anticipated unforeseen situations that are beyond the scope of physical development. Thus, it is crucial to determine if a pre-occupancy sustainable neighbourhood concept or a certified green project acknowledged sustainable dimension pillars (SDP) adaptive measures after occupancy. The purpose of the study was to identify the post-occupation township development's based on of sustainable criteria. The Stakeholders-Inclusion Approach and Post-Occupancy Evaluation Model were utilised as evaluation tools. This study's objective is to assess and classify the SDP gap in environmental, social, and economic responsiveness and balance methodology towards progressive developments in sustainable and resilient neighbourhood development at the community and individual levels. The respondents of this study are end-users or homeowners who have resided in these developments for over a year. In post-occupancy sustainable neighbourhoods, the findings revealed SDP adaptation gaps. As a result, it provides significant identified criteria measures for further improvement and refinement towards the development of a resilient and sustainable ASEAN neighbourhood.